Formation of apatite in simulated body fluid - Fan Dong-hui; Xu Zheng; Li Shi-pu; Yan Yu-hua (2010)
It is confirmed that the. essential condition for glmses and glass-ceramix:s to bond to living bone is the, formation of an apatite layer on their surfaces in the body. It is proposed ttua a hydrated silica f~rmed on the surfaces of these materials in the. body plays an important role in forming the surface apatite la)er , which h~s no, been proved yet. It is shown experirnentally that, a pure hydrated silica gel can induce the atuaite formation on its surface in a simulozext body fluid when its starting pH is irwreased from 7.2 to 7.4.